2011
DOI: 10.1007/s12253-011-9379-6
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Remission in Localized Diffuse Large B-cell Lymphoma

Abstract: Diffuse large B-cell lymphoma (DLBCL) is an aggressive neoplastic disease of the lymphatic system, the activated B-cell type of this disease is likely to have a substantially worse prognosis. In this study, we report the favorable outcome of the activated B-cell type of DLBCL, though untreated, 7 years after diagnosis. In 2003, DLBCL localized to the root of tongue was found in the patient complaining of dysphonia and a pharyngeal globus perception but the patient did not agree to get any active hematological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Again he assumed that the surgery (and the subsequent inflammation) stimulated/ triggered the host immune response and eliminated the rest of the tumor cells. Spontaneous remission has also been frequently observed in patients with concomitant viral infections, such as human immunodeficiency virus and Epstein-Barr virus [31,32]. Interestingly, our patient has HIV and HCV infection, which could serve as a plausible mechanism for regression.…”
Section: Immune Response Mechanismmentioning
confidence: 59%
“…Again he assumed that the surgery (and the subsequent inflammation) stimulated/ triggered the host immune response and eliminated the rest of the tumor cells. Spontaneous remission has also been frequently observed in patients with concomitant viral infections, such as human immunodeficiency virus and Epstein-Barr virus [31,32]. Interestingly, our patient has HIV and HCV infection, which could serve as a plausible mechanism for regression.…”
Section: Immune Response Mechanismmentioning
confidence: 59%
“…This has been documented in primary cutaneous DLBCL of the leg, as well as DLBCL of the bladder, breast, and conjunctiva . Extranodal onset may confer a greater likelihood of spontaneous regression . One case series found that regression is more likely to occur if there is a decrease in the size of the mass within the first two weeks after biopsy, which may be a predictor of spontaneous regression …”
Section: Discussionmentioning
confidence: 98%
“…Although commonly seen in nodal areas, DLBCL can occur in essentially any tissue of the body and is typically lethal within two years of diagnosis without treatment . Spontaneous regression is a rare but documented phenomenon that is more common in low grade phenotypes Primary non‐Hodgkin lymphoma of the bone is also rare, accounting for 5% of extranodal lymphoma and less than 1% of non‐Hodgkin's lymphoma .…”
Section: Discussionmentioning
confidence: 99%
“…Ferritin, sIL-2R, and LDH are all elevated in malignant lymphoma [8]. Indeed, elevation of LDH is one of the worst prognostic factors for EBV-positive DLBCL of the elderly [3].…”
Section: Discussionmentioning
confidence: 99%